Juridical Review of Waqf Land Disputes Due to Transition as Public Facilities (Disputes and solutions) - Tarigan, Tety Marlina; lubis, fauziah (Faculty of Law, Universitas Pekalongan, 2024)
Waqf as an integral part of Islamic teachings is a guideline for social worship which requires the separation and/or handover of part of the assets belonging to the waqf to be utilized in accordance with sharia, as regulated in Law Number 41 of 2004. The main purpose of waqf is devotion to Allah SWT and devotion. public. However, waqf practices often do not run in an orderly and efficient manner, as evidenced by the lack of data collection which causes many waqf assets to be poorly maintained and even transferred to third parties unlawfully. This research uses a descriptive method with a juridical-sociological approach. The focus is to understand the procedures, situations and views of the community regarding waqf practices, as well as measuring the effectiveness of the law in handling waqf disputes. It is hoped that the research results can provide further understanding of the challenges and solutions in managing waqf in society, as well as support efforts to advance the goals of waqf, which are actually for worship and general welfare in accordance with Islamic sharia. The aim of this research is to find out how Agrarian law works in the case of Waqf Land Disputes resulting from the Transition as Public Facilities.